Strategies for the Synthesis of Mono- and Bis-Thionaphthoquinones - de Carvalho, Alcione S.; da Rocha, David R.; Ferreira, Vitor F. (Current Organic Synthesis, 2021)
The subclass of compounds that have the nucleus 1, 4-naphthoquinone is the most diverse class of quinones, which have a large number of substances and have useful applications ranging from medicinal chemistry to application in materials with special properties. The introduction of one or two substituents with the sulfur heteroatom in the naphthoquinone nucleus generates products containing alkyl and aryl groups that amplify certain biological properties against bacteria, viruses, and fungi. There are several methods of preparing these compounds, mainly from low molecular weight naphthoquinones with two electrophilic sites capable of reacting with sulfides generating diversity and new classes of compounds, including new sulfur heterocycles and sulfur heterocycles fused with naphthoquinones. These compounds have been shown to be bioactive against several biological targets. This review will describe the methods of their synthesis and, when applicable, their biological activities.
Keywords: thionaphthoquinone